Resource selection in reintroduced lions and the influence of intergroup interactions. (22nd October 2018) - Yiu, S. W.; Karczmarski, L.; Parrini, F.; Keith, M.
Abstract: Optimal resource selection is crucial for maximising fitness and survival. Animals introduced to a new area need time to explore the environment, which could result in a time lag before optimal selection occurs. Furthermore, intra‐specific interactions (particularly in territorial species) also play a role in shaping resource selection patterns, with weaker individuals being displaced from optimal resources. We assessed within‐home range habitat selection of lions ( Panthera leo ) introduced to a South African wildlife reserve, to examine changes in their resource selection patterns across 3 years from the time of introduction, and the effect of intra‐specific interactions on these selection patterns. After initial exploration, lions selected low altitudes and flat slopes that facilitate movement, high tree densities that provide cover and refuge, and areas close to water sources and flood plains that have high prey density. Responses to human disturbances differed between males and females, with males being more tolerant to high densities of roads and buildings. These patterns were however disrupted by deaths due to intergroup conflicts and by introductions of new individuals, with the dominant groups remaining within favourable resources and subordinate groups shifting to suboptimal resources. Our findings support the spatio‐temporal dynamic nature of habitat selection processes for reintroduced large carnivores and emphasize the role of intra‐specific interactions in influencing the landscape determinants of habitat selection. Abstract : Reintroduced animals must learn the distribution of resources in the landscape in order to survive in a new environment. We studied the resource selection of reintroduced lions and showed how the patterns changed over time during the processes of adapting to the environment. The patterns were disrupted by territorial conflicts and the introductions of new individuals, highlighting the importance of intergroup interactions in influencing resource selection in reintroduced large carnivores.